Measurement of the Lambda(0)(b), Xi(-)(b), and Omega(-)(b) Baryon Masses - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
Bottom baryons decaying to a J/ψ meson and a hyperon are reconstructed using 1.0 fb-1 of data collected in 2011 with the LHCb detector. Significant Λb0→J/ψΛ, Ξb-→J/ψΞ- and Ωb-→J/ψΩ- signals are observed and the corresponding masses are measured to be M(Λb0)=5619.53±0.13(stat.) ±0.45(syst.) MeV/c2, M(Ξb-)=5795.8±0.9(stat.)±0.4(syst.) MeV/c2, M(Ωb-)=6046.0±2.2(stat.)±0.5(syst.) MeV/c2, while the differences with respect to the Λb0 mass are M(Ξb-)-M(Λb0)= 176.2±0.9(stat.)±0.1(syst.) MeV/c2, M(Ωb-)-M(Λb0)= 426.4±2.2(stat.)±0.4(syst.) MeV/c2. These are the most precise mass measurements of the Λb0, Ξb- and Ωb- baryons to date. Averaging the above Λb0 mass measurement with that published by LHCb using 35 pb-1 of data collected in 2010 yields M(Λb0)=5619. 44±0.13(stat.)±0.38(syst.) MeV/c2. © 2013 CERN. Published by the American Physical Society under the terms of the.